Workation –Analysis of Challenges and Opportunities in the Evolving Paradigm of Remote Work - Paweł ŁUCZAK (Communications of International Proceedings, 2024)
Workation, combining work with vacation, is a new trend that has gained popularity during the COVID-19 pandemic, mainly due to flexible forms of work, such as remote work. This model allows employees to perform their professional duties from anywhere in the world, while also taking advantage of the opportunity to travel and rest. It is particularly attractive to younger employees who appreciate the balance between work and private life. Implementing the workation concept brings numerous challenges for organizations. The aim of this article is to fill the cognitive gap in the challenges of implementing the workation concept in an organization. While workation offers benefits in the form of flexibility and potential improvement in work-life balance, it requires a careful approach to risk analysis and implementation of appropriate management practices. The key is to adapt legal and organizational regulations, as well as support employees in effectively using this form of work. This trend remains an area for further research, especially in the context of its impact on team dynamics and work efficiency.
Keywords: workation; challenges; remote work; trends